Shifts among Eukaryota, Bacteria, and Archaea define the vertical organization of a lake sediment - Wurzbacher, Christian; Fuchs, Andrea; Attermeyer, Katrin; Frindte, Katharina; Grossart, Hans-Peter; Hupfer, Michael; Casper, Peter; Monaghan, Michael T. (Microbiome, 2017)
Lake sediments harbor diverse microbial communities that cycle carbon and nutrients while being constantly colonized and potentially buried by organic matter sinking from the water column. The interaction of activity and burial remained largely unexplored in aquatic sediments. We aimed to relate taxonomic composition to sediment biogeochemical parameters, test whether community turnover with depth resulted from taxonomic replacement or from richness effects, and to provide a basic model for the vertical community structure in sediments. We analyzed four replicate sediment cores taken from 30-m depth in oligo-mesotrophic Lake Stechlin in northern Germany. Each 30-cm core spanned ca. 170 years of sediment accumulation according to Cs dating and was sectioned into layers 1-4 cm thick. We examined a full suite of biogeochemical parameters and used DNA metabarcoding to examine community composition of microbial Archaea, Bacteria, and Eukaryota. Community β-diversity indicated nearly complete turnover within the uppermost 30 cm. We observed a pronounced shift from Eukaryota- and Bacteria-dominated upper layers (<5 cm) to Bacteria-dominated intermediate layers (5-14 cm) and to deep layers (>14 cm) dominated by enigmatic Archaea that typically occur in deep-sea sediments. Taxonomic replacement was the prevalent mechanism in structuring the community composition and was linked to parameters indicative of microbial activity (e.g., CO and CH concentration, bacterial protein production). Richness loss played a lesser role but was linked to conservative parameters (e.g., C, N, P) indicative of past conditions. By including all three domains, we were able to directly link the exponential decay of eukaryotes with the active sediment microbial community. The dominance of Archaea in deeper layers confirms earlier findings from marine systems and establishes freshwater sediments as a potential low-energy environment, similar to deep sea sediments. We propose a general model of sediment structure and function based on microbial characteristics and burial processes. An upper "replacement horizon" is dominated by rapid taxonomic turnover with depth, high microbial activity, and biotic interactions. A lower "depauperate horizon" is characterized by low taxonomic richness, more stable "low-energy" conditions, and a dominance of enigmatic Archaea.